The Once-Only Principle The TOOP Project - Krimmer, Robert; Prentza, Andriana; Mamrot, Szymon (Information Systems and Applications, incl. Internet/Web, and HCI,, 2021)
This open access State-of-the-Art Survey describes and documents the developments and results of the Once-Only Principle Project (TOOP). The Once-Only Principle (OOP) is part of the seven underlying principles of the eGovernment Action Plan 2016-2020. It aims to make the government more effective and to reduce administrative burdens by asking citizens and companies to provide certain standard information to the public authorities only once. The project was horizontal and policy-driven with the aim of showing that the implementation of OOP in a cross-border and cross-sector setting is feasible. The book summarizes the results of the project from policy, organizational, architectural, and technical points of view. This book has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement No 737460.